Amarogentin regulates self renewal pathways to restrict liver carcinogenesis in experimental mouse model. Issue 7 (8th July 2015) - Sur, Subhayan; Pal, Debolina; Banerjee, Kaustav; Mandal, Suvra; Das, Ashes; Roy, Anup; Panda, Chinmay Kumar
Abstract : Amarogentin, a secoiridoid glycoside isolated from medicinal plant Swertia chirata, was found to restrict CCl4 /N‐nitrosodiethyl amine (NDEA) induced mouse liver carcinogenesis by modulating G1/S cell cycle check point and inducing apoptosis. To understand its therapeutic efficacy on stem cell self renewal pathways, prevalence of CD44 positive cancer stem cell (CSC) population, expressions (mRNA/protein) of some key regulatory genes of self renewal Wnt and Hedgehog pathways along with expressions of E‐cadherin and EGFR were analyzed during the liver carcinogenesis and in liver cancer cell line HepG2. It was observed that amarogentin could significantly reduce CD44 positive CSCs in both pre and post initiation stages of carcinogenesis than carcinogen control mice. In Wnt pathway, amarogentin could inhibit expressions of β‐catenin, phospho β‐catenin (Y‐654) and activate expressions of antagonists sFRP1/2 and APC in the liver lesions. In Hedgehog pathway, decreased expressions of Gli1, sonic hedgehog ligand, and SMO along with up‐regulation of PTCH1 were seen in the liver lesions due to amarogentin treatment. Moreover, amarogentin could up‐regulate E‐cadherin expression and down‐regulate expression of EGFR in the liver lesions. Similarly, amarogentin could inhibit HepG2 cell growth along with expression and prevalence of CD44 positive CSCs. Similar to in vivo analysis, amarogentin could modulate the expressions of the key regulatory genes of the Wnt and hedgehog pathways and EGFR in HepG2 cells. Thus, our data suggests that the restriction of liver carcinogenesis by amarogentin might be due to reduction of CD44 positive CSCs and modulation of the self renewal pathways. © 2015 Wiley Periodicals, Inc.